Organizational change management: theoretical and practical aspects - Korsakienė, Renata (Business: Theory and Practice, 2006)
The processes of globalization, new technologies, intense competition and the internal environment of organisations predetermine organisational changes which have the main purpose to adapt to the changing environment. Therefore organisational change management has become the topical issue of today’s business companies. The paper analyses the aspects of organisational change management. The results of a survey of organisational change management are analysed. At the end of the paper the results of the survey are summarized and the conclusions are presented.Article in Lithuanian.Organizacinių pokyčių valdymas: teoriniai ir praktiniai aspektaiSantrauka. Globalizacijos procesai, naujos technologijos, intensyvi konkurencija, taip pat pačios organizacijos vidinė aplinka lemia organizacinius pokyčius, kurių tikslas – adaptuotis prie kintančios aplinkos. Todėl organizacinių pokyčių valdymas tampa aktualus šiandienos verslo įmonėms. Šiame straipsnyje nagrinėjami organizacinių pokyčių valdymo aspektai, analizuojami organizacinių pokyčių valdymo tyrimo rezultatai. Straipsnio pabaigoje apibendrinami tyrimo rezultatai ir pateikiamos išvados.Reikšminiai žodžiai: organizaciniai pokyčiai, išoriniai veiksniai, vidiniai veiksniai, lyderiavimas, motyvavimas, komunikacija.